A Study of Double Consciousness in Lauri Lemberg's St. Croix Avenue and Paula Ivaska Robbins' Below Rollstone Hill - Ghasemi Mehdi (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2022)
In this paper, I analyse the Du Boisian concept of 'double consciousness' and offer an overview of its different implications. I then approach Lauri Lemberg's St. Croix Avenue and Paula Ivaska Robbins' Below Rollstone Hill from the perspective of this concept. A comparative study of these novels enables me to detect and contextualise cases of double consciousness within both texts as related to Finnish immigrants in the United States. I also argue how this 'double consciousness' affects the lives and ethnic identities of Finnish immigrant characters. In line with a contextual analysis, a textual analysis in the form of close reading will also be undertaken in order to offer a better understanding of the functions of 'double consciousness' for Finnish characters in both literary works.